2020
DOI: 10.4049/immunohorizons.1900077
|View full text |Cite
|
Sign up to set email alerts
|

Norethisterone Enanthate Increases Mouse Susceptibility to Genital Infection with Herpes Simplex Virus Type 2 and HIV Type 1

Abstract: Norethisterone enanthate (NET-EN) and depot-medroxyprogesterone acetate (DMPA) are two forms of injectable progestin used for contraception. Whereas clinical research indicates that women using DMPA are more susceptible to HIV and other genital pathogens, causal relationships have not been determined. Providing an underlying mechanism for this connection, however, is recent work that showed DMPA weakens genital mucosal barrier function in mice and humans and respectively promotes susceptibility of wild-type an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 58 publications
(65 reference statements)
1
8
0
Order By: Relevance
“…While we are currently exploring the latter possibility in RM SIV challenge studies, our current findings already establish that DMPA-mediated changes to genital epithelial integrity and barrier function are reversed by concomitant administration of E-containing compounds. These results are congruent with mouse model data that showed combined treatment with progestin and E avoided the compromise of genital epithelial barrier function and uniform susceptibility to genital HSV-2 or HIV-1 infection produced by DMPA treatment alone [ 12 , 13 , 18 ]. Whereas RM administered DMPA or DMPA and E had comparable stratum corneum thickness, exogenous E prevented DMPA-mediated increases in genital epithelial permeability.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…While we are currently exploring the latter possibility in RM SIV challenge studies, our current findings already establish that DMPA-mediated changes to genital epithelial integrity and barrier function are reversed by concomitant administration of E-containing compounds. These results are congruent with mouse model data that showed combined treatment with progestin and E avoided the compromise of genital epithelial barrier function and uniform susceptibility to genital HSV-2 or HIV-1 infection produced by DMPA treatment alone [ 12 , 13 , 18 ]. Whereas RM administered DMPA or DMPA and E had comparable stratum corneum thickness, exogenous E prevented DMPA-mediated increases in genital epithelial permeability.…”
Section: Discussionsupporting
confidence: 87%
“…Evaluation of the barrier function of vaginal mucosal epithelium was performed as previously described [ 12 , 13 , 18 , 19 ]. In summary, fresh vaginal biopsies were placed in chilled transport medium and transferred to sterile 96-well plates.…”
Section: Methodsmentioning
confidence: 99%
“…Our RNA-seq data revealed that several genes associated with cell-cell adhesion, including desmosome function ( DSG1 , DSC1 , DSC2 , PKP1 , PKP3 , JUP , DSP ), were downregulated in the DMPA group ( S2 Table ). Among these, suppressed expression of DSG1 has been associated with DMPA use also in other human and animal models [ 15 , 16 , 22 , 29 , 30 ]. The DSG1 -encoded protein desmoglein-1 ( DSG1 : DMPA vs controls, top-15 downregulated genes, Table 2 ) and the CLDN1 -encoded protein claudin-1 ( CLDN1 : DMPA vs controls, no significant differential expression at the gene level, FDR adj.…”
Section: Resultsmentioning
confidence: 99%
“…These results implied that the increased epithelial permeability induced by DMPA or LNG has a more prominent role in promoting mouse HSV-2 susceptibility than progestin-mediated changes in epithelial thinning. In addition to promoting genital HSV-2 infection, we also found that treatment of wild-type mice with LNG increased susceptibility to genital Chlamydia trachomatis infection and treatment of humanized mice with DMPA or NET-EN induced uniform susceptibility to genital inoculation with cell-associated HIV-1 [ 33–35 ]. Interestingly, DMPA treatment of mice also enhanced genital expression of multiple kallikreins [ 33 ], serine proteases that promote degradation of desmosomal proteins [ 20 , 21 ].…”
Section: Hiv Progestins and Barrier Function: An Evidence-based Casmentioning
confidence: 99%
“…In addition to promoting genital HSV-2 infection, we also found that treatment of wild-type mice with LNG increased susceptibility to genital Chlamydia trachomatis infection and treatment of humanized mice with DMPA or NET-EN induced uniform susceptibility to genital inoculation with cell-associated HIV-1 [ 33–35 ]. Interestingly, DMPA treatment of mice also enhanced genital expression of multiple kallikreins [ 33 ], serine proteases that promote degradation of desmosomal proteins [ 20 , 21 ]. These results implied that DMPA-mediated changes in kallikrein protease expression promoted the lower levels of desmosomal proteins and loss of genital epithelial barrier function seen in treated animals.…”
Section: Hiv Progestins and Barrier Function: An Evidence-based Casmentioning
confidence: 99%